2002
DOI: 10.1080/02643290143000141
|View full text |Cite
|
Sign up to set email alerts
|

The syntax of single words: Evidence from a patient with a selective function word reading deficit

Abstract: We describe the reading performance of a patient who has selective deficits for reading nonwords, function words, and morphologically complex words in isolation. His reading of highly abstract nouns and verbs, however, is relatively well preserved. He can recognise and comprehend the meaning of written function words, of derivational morphology, and of most inflectional morphology. We suggest that his deficit in reading grammatical morphemes is unrelated to his problems in reading nonwords and cannot be explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 59 publications
0
11
1
Order By: Relevance
“…Note, however, that the interpretation proposed here for CB's impairment contrasts with the cases described by Druks and Froud (2002) and by Berndt and Haendiges (2000) in at least two respects. First of all, in CB's case the impairment would be due to a deficient activation of closedclass items by an appropriately retrieved sentence structure.…”
contrasting
confidence: 44%
“…Note, however, that the interpretation proposed here for CB's impairment contrasts with the cases described by Druks and Froud (2002) and by Berndt and Haendiges (2000) in at least two respects. First of all, in CB's case the impairment would be due to a deficient activation of closedclass items by an appropriately retrieved sentence structure.…”
contrasting
confidence: 44%
“…The aphasic subject MC provided such a testing opportunity, in the single-word reading modality, because he was totally unable to read any functional items (including determiners, complementisers, quantifiers, inflectional elements, wh-words, pronouns, negation and conjunctions) in sharp contrast with his relatively intact reading of substantives (Druks and Froud, 2002;Froud, 2001a,b). MC has already provided opportunities to investigate the lexical/functional status of various categories, including adverbials (Froud, 2001a) and prepositions (Froud, 2001b).…”
Section: Introductionmentioning
confidence: 99%
“…His high error rate overall on this task was largely due to his tendency to add an indefinite article to the bare nouns, rather than to errors on the target words themselves). Additionally, we have demonstrated that MC's comprehension of written function words in isolation was intact (so far as this is possible to test); so that he recognized functional items, and knew what they meant, even when he was completely unable to read them (Druks and Froud, 2002). MC's ability to produce these same categories in connected speech was hypothesized to be supported by the availability of lexical information for substantives, presumably including their extended projections, so that production of functional categories in connected speech, or in a sentential context, or in reading of connected text, is bolstered by the availability of the syntactic frame.…”
mentioning
confidence: 99%
See 2 more Smart Citations